Downregulation of circFASTKD1 ameliorates myocardial infarction by promoting angiogenesis - Gao, Wen-Qing (Aging (Albany NY), 2020)
Circular RNAs (circRNAs), a novel class of endogenous long non-coding RNAs, have attracted considerable attention due to their closed continuous loop structure and potential clinical value. In this study, we investigated the function of circFASTKD1 in vascular endothelial cells. CircFASTKD1 bound directly to miR-106a and relieved its inhibition of Large Tumor Suppressor Kinases 1 and 2, thereby suppressing the Yes-Associated Protein signaling pathway. Under both normal and hypoxic conditions, the ectopic expression of circFASTKD1 reduced the viability, migration, mobility and tube formation of vascular endothelial cells, whereas the downregulation of circFASTKD1 induced angiogenesis by promoting these processes. Moreover, downregulation of circFASTKD1 in mice improved cardiac function and repair after myocardial infarction. These findings indicate that circFASTKD1 is a potent inhibitor of angiogenesis after myocardial infarction and that silencing circFASTKD1 exerts therapeutic effects during hypoxia by stimulating angiogenesis in vitro and in vivo.